The effects of different styles of musical auditory stimulation on cardiac autonomic regulation in healthy women - Roque, Adriano L.; Valenti, Vitor Engrácia [UNESP]; Guida, Heraldo Lorena [UNESP]; Campos, Mônica F. [UNESP]; Knap, André [UNESP]; Vanderlei, Luiz Carlos M. [UNESP]; Ferreira, Celso; Abreu, Luiz Carlos de [UNESP] (Wolters Kluwer, 2013)
The literature investigated the effects of chronic baroque music auditory stimulation on the cardiovascular system. However, it lacks in the literature the acute effects of different styles of music on cardiac autonomic regulation. To evaluate the acute effects of baroque and heavy metal music on heart rate variability (HRV) in women. The study was performed in 21 healthy women between 18 and 30 years old. We excluded persons with previous experience with music instrument and those who had affinity with the song styles. All procedures were performed in the same sound-proof room. We analyzed HRV in the time (standard deviation of normal-to-normal respiratory rate (RR) intervals, root-mean square of differences between adjacent normal RR intervals in a time interval, and the percentage of adjacent RR intervals with a difference of duration greater than 50 ms) and frequency (low frequency [LF], high frequency [HF], and LF/HF ratio) domains. HRV was recorded at rest for 10 min. Subsequently they were exposed to baroque or heavy metal music for 5 min through an earphone. After the first music exposure they remained at rest for more 5 min and them they were exposed again to baroque or heavy metal music. The sequence of songs was randomized for each individual. The power analysis provided a minimal number of 18 subjects. Shapiro-Wilk to verify normality of data and analysis of variance for repeated measures followed by the Bonferroni test for parametric variables and Friedman's followed by the Dunn's post-test for non-parametric distributions. During the analysis of the time-domain indices were not changed. In the frequency-domain analysis, the LF in absolute units was reduced during the heavy metal music stimulation compared to control. Acute exposure to heavy metal music affected the sympathetic activity in healthy women.
Keywords: Auditory stimulation; Autonomic nervous system; Cardiovascular system; Music; adolescent; adult; analysis of variance; auditory stimulation; autonomic nervous system; classification; controlled clinical trial; controlled study; female; heart rate; human; music; physiology; randomized controlled trial; time; Acoustic Stimulation; Adolescent; Adult; Analysis of Variance; Autonomic Nervous System; Female; Heart Rate; Humans; Time Factors; Young Adult